Transforming the quality assurance framework for Taiwanese higher education: A glonacal context. Issue 3 (1st September 2014) - Hou, Angela Yung-Chi; Chen, Karen Hui-Jung; Morse, Robert
Abstract: In an interconnected world, higher education systems, the institutions that comprise them, educational policy makers, quality assurance agencies are all supposed to interact simultaneously in a global, national, and local, or glonacal, context. Like some other Asian nations, Taiwan has been developing its glonacal quality assurance framework. At the same time, it attempted to give more institutional autonomy to universities by awarding them a self-accreditation status. The main purpose of the paper is to examine transformation of QA systems in Taiwan's higher education under the glonacal context and to analyze the new development of self-accreditation.